2006
DOI: 10.1371/journal.pbio.0040365
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Impairs Reverse Cholesterol Transport from Macrophages

Abstract: Several steps of HIV-1 replication critically depend on cholesterol. HIV infection is associated with profound changes in lipid and lipoprotein metabolism and an increased risk of coronary artery disease. Whereas numerous studies have investigated the role of anti-HIV drugs in lipodystrophy and dyslipidemia, the effects of HIV infection on cellular cholesterol metabolism remain uncharacterized. Here, we demonstrate that HIV-1 impairs ATP-binding cassette transporter A1 (ABCA1)-dependent cholesterol efflux from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
293
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 282 publications
(326 citation statements)
references
References 75 publications
32
293
0
1
Order By: Relevance
“…1H). This ultrastructural appearance was similar to the macrophages identified in the lungs as a result of several infectious agents including HIV and tuberculosis [21,22]. Ultrastructural analysis of days 13-15 PI granular macro-phages (Fig.…”
Section: Bal-derived Lung Macrophagessupporting
confidence: 69%
“…1H). This ultrastructural appearance was similar to the macrophages identified in the lungs as a result of several infectious agents including HIV and tuberculosis [21,22]. Ultrastructural analysis of days 13-15 PI granular macro-phages (Fig.…”
Section: Bal-derived Lung Macrophagessupporting
confidence: 69%
“…Of note, the HIV-1 Nef protein can impair ABCA1 cholesterol efflux from macrophages, thus supporting atherosclerosis. This viral inhibition of efflux was correlated with a direct interaction between ABCA1 and Nef Mujawar et al 2006). More recently it was shown that Nef downregulates ABCA1 function by a posttranslational mechanism that stimulates ABCA1 degradation but does not require the ability of Nef to bind ABCA1 .…”
Section: Hiv Infectionmentioning
confidence: 88%
“…It has been suggested that Nef enhances HIV-1 infectivity by increasing the cholesterol content of progeny virions, based on the observation that Nef impaired the efflux of cholesterol from macrophages by down-regulating the ATP-binding cassette transporter A1 (55). However, our results argue against the possibility that Dyn2 is required for a Nef-mediated increase in virion cholesterol, because Dyn2(K 44 A) did not counteract the effect of Nef but rather appeared to moderately increase virion cholesterol levels (SI Fig.…”
Section: Discussionmentioning
confidence: 99%